2011
DOI: 10.1186/1471-2202-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Error-dependent modulation of speech-induced auditory suppression for pitch-shifted voice feedback

Abstract: BackgroundThe motor-driven predictions about expected sensory feedback (efference copies) have been proposed to play an important role in recognition of sensory consequences of self-produced motor actions. In the auditory system, this effect was suggested to result in suppression of sensory neural responses to self-produced voices that are predicted by the efference copies during vocal production in comparison with passive listening to the playback of the identical self-vocalizations. In the present study, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
137
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 40 publications
20
137
2
Order By: Relevance
“…Physiology studies have documented this modulatory effect as speaking-induced auditory suppression, revealed by a decrease in the amplitude of the N100 event-related potentials (ERPs) in response to feedback pitch perturbations during speaking compared with playback (Behroozmand and Larson, 2011; Flinker et al, 2010; Heinks-Maldonado et al, 2005; Houde et al, 2002). A number of other studies have reported that auditory suppression has been reduced when subjects produced rapid and complex speech (Ventura et al, 2009), spoke in a foreign language (Simmonds et al, 2011) or stuttered (Beal et al, 2011), indicating an increased demand for processing auditory feedback information during speech production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Physiology studies have documented this modulatory effect as speaking-induced auditory suppression, revealed by a decrease in the amplitude of the N100 event-related potentials (ERPs) in response to feedback pitch perturbations during speaking compared with playback (Behroozmand and Larson, 2011; Flinker et al, 2010; Heinks-Maldonado et al, 2005; Houde et al, 2002). A number of other studies have reported that auditory suppression has been reduced when subjects produced rapid and complex speech (Ventura et al, 2009), spoke in a foreign language (Simmonds et al, 2011) or stuttered (Beal et al, 2011), indicating an increased demand for processing auditory feedback information during speech production.…”
Section: Discussionmentioning
confidence: 99%
“…EEG, MEG, ECoG) of speech production and motor control in an auditory feedback perturbation paradigm (Behroozmand and Larson, 2011; Behroozmand et al, 2011, 2009; Chang et al, 2013; Flinker et al, 2010; Greenlee et al, 2013, 2011; Heinks-Maldonado et al, 2006, 2005; Houde et al, 2002; Sitek et al, 2013). Results of these studies showed that the motor act of speaking modulates speech sound processing in auditory cortical areas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies [62,63,64,65], the authors conducted an ERP and FAF(frequencyaltered feedback)experiment in order to findt he ERP neural sensory components involved in the pitch shift reflex. In Hawco studies [62] the participants vocalized for 3s ,w hile subjected to modifieda uditory feedback.…”
Section: Vol 99 (2013)mentioning
confidence: 99%